2017
DOI: 10.20431/2454-6224.0301005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Treatments on Macro and Microelement Contents of Oil Sunflower (Helianthus annuus L.) Seeds

Abstract: Abstract:The present study was carried out to investigate the effects of different nitrogenous fertilizer treatments through soil (0, 30, 60, 90, 120 and 150 kg N ha -1 ) on macro and micro nutrient (N, P, K, Ca, Mg, Fe, Zn, Mn, Cu and B)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Ai et al [41] found that Cu and Mn concentrations in the aboveground tissues of Bothriochloa ischaemum increased significantly with N addition. The determined trends of changes in the Fe, Mn and Cu contents may vary with N nutrition intensity [42] as observed in this study.…”
Section: Discussionsupporting
confidence: 64%
“…Ai et al [41] found that Cu and Mn concentrations in the aboveground tissues of Bothriochloa ischaemum increased significantly with N addition. The determined trends of changes in the Fe, Mn and Cu contents may vary with N nutrition intensity [42] as observed in this study.…”
Section: Discussionsupporting
confidence: 64%